High Power Discharge Lamps and Their Photochemical Applications: An Evaluation of Pulsed Radiation - Bouslimi, Lotfi; Stambouli, Mongi; Braiek, Ezzedine Ben; Zissis, Georges; Cambronne, Jean Pascal (IntechOpen, 2012)
None